Designing Function-Specific Plant Systems for Sustainable Urban Development - French, Katherine E. (Frontiers in Sustainable Cities, 2021)
Increasingly, architects are embracing “biomorphic urbanism,” a design ideology that takes inspiration from nature to develop more sustainable cities that reduce the environmental impact of urban life. At the moment, plants are incorporated into biomorphic urban designs for conservation or aesthetic reasons. Here, I argue the role of plants in building more sustainable cities can be augmented by integrating plant sciences, ecology, and urban design. I propose that we can develop synthetic Function-Specific Plant Systems (FSPSs) which harness the genetic and metabolic diversity of plants to perform specific services that benefit society and the environment as a whole. FSPSs can contribute to three broad categories of urban life: Urban Landscape and Infrastructure; Biodiversity and the Environment; and Human Health. Across the three categories, FSPSs can be designed to provide nine key services: flood control, soil stabilization, fire control, climate control, water treatment, habitat for endangered flora and fauna, pest control, air purification, and modulation of human immune systems. The plants included in each FSPS are based on several considerations, including (1) functional traits, (2) biogeography, and (3) cultural concerns. In the future, synthetic biology could improve, expand and diversify these services. This approach harnesses plant biodiversity to transform urban spaces while meeting key UN Sustainable Development Goals.